2021
DOI: 10.3389/fphar.2020.636533
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipid Accumulation in Skeletal Muscle and Liver Cells: A Protective Mechanism of Bilirubin Against Diabetes Mellitus Type 2

Abstract: Ectopic lipid accumulation in skeletal muscle and liver drives the pathogenesis of diabetes mellitus type 2 (DMT2). Mild hyperbilirubinaemia has been repeatedly suggested to play a role in the prevention of DMT2 and is known for its capacity to shape an improved lipid phenotype in humans and in animals. To date, the effect of bilirubin on lipid accumulation in tissues that are prone to ectopic lipid deposition is unclear. Therefore, we analyzed the effect of bilirubin on lipid accumulation in skeletal muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In addition, bilirubin also inhibited cholesterol and cholesterol esters production, suggesting that bilirubin attenuates hepatic steatosis and atherosclerosis by interrupting cholesterol biosynthesis. Our findings are consistent with a previous study, which demonstrated mild hyperbilirubinemia conditions significantly reduced the intracellular lipid accumulation in C2C12 skeletal mouse muscle and HepG2 human liver cells [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, bilirubin also inhibited cholesterol and cholesterol esters production, suggesting that bilirubin attenuates hepatic steatosis and atherosclerosis by interrupting cholesterol biosynthesis. Our findings are consistent with a previous study, which demonstrated mild hyperbilirubinemia conditions significantly reduced the intracellular lipid accumulation in C2C12 skeletal mouse muscle and HepG2 human liver cells [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
“…Consistently, patients with Gilbert’s syndrome had reduced TC and LDL-C levels when compared to matched controls ( 19 , 28 , 29 ). Bilirubin could promote lipid catabolism and inhibit lipid accumulations ( 30 , 31 ). Bilirubin might bind to PPARα and promote β-hydroxybutyrate, and then activate hepatic β-oxidation pathway, thus boosting lipid metabolism ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of bilirubin to shape a health beneficial lipid and glucose phenotype has been demonstrated in several other animal models [7,11,[47][48][49] and in vitro studies [40,50]. Numerous large prospective epidemiological studies reported that bilirubin is associated with beneficial characteristics (improved BMI, blood lipids and insulin resistance) and a reduced risk of CVD and DMT2 [9,10,14,15,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 93%